1999
DOI: 10.1038/sj.bjc.6690425
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid nodular disease after radiotherapy to the neck for childhood Hodgkin’s disease

Abstract: SummaryPatients who receive radiotherapy to the neck are at risk of developing thyroid dysfunction. This prospective study of patients whose treatment for Hodgkin's disease in childhood included radiotherapy to the neck aimed to investigate the incidence and natural history of thyroid dysfunction and the morphological changes of the gland demonstrated on ultrasound. Forty-seven patients were investigated by clinical examination, thyroid function tests and thyroid ultrasound. Only six patients had a clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 20 publications
0
16
1
1
Order By: Relevance
“…For populations that are screened using more sensitive modalities, such as thyroid ultrasound, the absolute number of abnormalities detected as well as the frequency of multinodularity likely will be increased. 12,13,30 However, because thyroid ultrasound detects many small lesions, the majority of which are benign, it is expected that the incidence of thyroid malignancy would be lower than that observed in the current study. Because so many of the thyroid malignancies that are detected by ultrasound are small and of uncertain clinical significance, the role of ultrasound screening in irradiated populations remains an area of controversy.…”
Section: Discussioncontrasting
confidence: 53%
“…For populations that are screened using more sensitive modalities, such as thyroid ultrasound, the absolute number of abnormalities detected as well as the frequency of multinodularity likely will be increased. 12,13,30 However, because thyroid ultrasound detects many small lesions, the majority of which are benign, it is expected that the incidence of thyroid malignancy would be lower than that observed in the current study. Because so many of the thyroid malignancies that are detected by ultrasound are small and of uncertain clinical significance, the role of ultrasound screening in irradiated populations remains an area of controversy.…”
Section: Discussioncontrasting
confidence: 53%
“…Studies on patients receiving irradiation treatment for various cancers have reported a high frequency of benign and malignant thyroid nodules. The reported relative risks for thyroid nodules among the survivors of pediatric cancers who have undergone radiation therapy vary greatly, with an incidence of malignancy of 10-40% (6,7,8,9,10,11,12,13). Analysis of studies evaluating thyroid carcinoma after exposure to external radiation during childhood showed that the dose-response relationship was linear, although the risk appeared to plateau at the highest dose, with risk appearing to slightly decrease at doses of even more than 2000 cGy (9,11,13,14,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Morphologic changes to the thyroid gland after XRT, such as the development of solid or cystic masses, are well documented by sonography and histology. [13][14][15][16][17][18] The thyroid gland is known to decrease in the size after XRT as demonstrated by sonography. 18 Patients with laryngeal cancer are followed after treatment with CT of the neck to evaluate treatment response and monitor for recurrence; however, radiologists rarely mention changes in the size of the thyroid gland on follow-up CT reports following XRT for head and neck cancer.…”
mentioning
confidence: 99%